Increased Internet use and poorer ability to manage emotions in youth at high-risk for psychosis - Pelletier-Baldelli, Andrea (Schizophr Res Cogn, 2015)
The relationship between Internet use and social behavior remains unknown. However, research indicates that Internet use (IU) may have some causal role in certain types of psychopathology and overall functioning. In contrast, other work suggests that IU may be protective and buffer against social isolation. Poorer emotional processing (EP) is characteristic of schizophrenia, and these deficits are present prior to illness onset (the ultra high-risk period (UHR)). UHR adolescents/young adults also fall within an age demographic characterized by extensive IU, which suggests that evaluating a link between IU and social behavior in this population may be especially informative. The present study examined the relationship between IU and emotional processing in 98 adolescents/young adults (52 UHR youth and 46 controls). UHR youth exhibited greater problematic IU (β = − 6.49, F(1,95) = 8.79, p = 0.002) and social withdrawal/problems resulting from this use (β = − 3.23, F(1,95) = 11.43, p < 0.001), as well deficits in emotional processing in comparison to healthy peers (β = 4.59, F(1,94) = 5.52, p = 0.011). Furthermore, the social problems resulting from IU were significantly related to the ability to process emotional information in the UHR group (β = − 0.51, t(1,48) = − 2.10, p = 0.021). UHR youth showed evidence of problematic IU relative to controls, and the social problems resulting from IU related to poorer EP. Findings replicate extant research involving other psychosis risk populations, while adding information regarding how social processes may relate to IU.